Pelatihan Kewirausahaan Keripik Bote Berbasis Digital Marketing bagi Pengurus Ranting Muhammadiyah Sutorejo - Irwansyah, Irwansyah; Desipradani, Gita; Da’im, Suli (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the entrepreneurial skills of the Muhammadiyah Sutorejo branch administrators and their ability to utilize digital technology for marketing Bote Chips products. The implementation method employed in this program was Participatory Rural Appraisal (PRA), involving 15 participants who are branch administrators with no prior experience in entrepreneurship. The program activities included training in digital marketing, branding, and market analysis, as well as a demonstration of the use of a slicing machine to improve production efficiency. The data analysis technique used in this evaluation was qualitative analysis, with data collected through observation and direct interaction with participants. The results of the program indicated an increase in participants’ knowledge of digital marketing and operational skills in using the Keripik Bote processing machine. Participants demonstrated a high level of enthusiasm and readiness to apply the knowledge gained to their entrepreneurial efforts. This program is expected to contribute to increased sales turnover and competitiveness of Keripik Bote products in the market. Thus, the training provides knowledge and promotes economic self-reliance among the members of the Muhammadiyah Sutorejo branch